Design and testing of composite compressor blades with focus on the vibration behaviour. (January 2017) - Wollmann, T.; Modler, N.; Dannemann, M.; Langkamp, A.; Nitschke, S.; Filippatos, A.
Abstract: Increasing demands on the performance of rotating components as well as on the noise reduction in jet engines have led to higher dynamic requirements. Composite materials can contribute to a reduction of vibration amplitudes due to their inherent advantageous damping behaviour and their high specific stiffness. A numerical prediction of the vibration behaviour is necessary for an efficient use of composite materials in rotors, especially since the modal parameters such as the eigenfrequency and the modal damping are influenced by the fibre orientation. For this investigation, a composite compressor blade was designed with a focus on its vibration behaviour. The modal parameters were numerically predicted and experimentally validated. The damping of composites was taken into account using the strain energy method. Utilising this method, the modal damping parameters of the compressor blade were calculated based on direction-dependent material properties of single unidirectional carbon fibre-reinforced epoxy layers.